EMRinger: side chain–directed model and map validation for 3D cryo-electron microscopy - Barad, Benjamin A; Echols, Nathaniel; Wang, Ray Yu-Ruei; Cheng, Yifan; DiMaio, Frank; Adams, Paul D; Fraser, James S (Nature methods, 2015)
The fit of atomic models of protein structures to high-resolution cryo-electron microscopy maps can be assessed with a validation tool, EMRinger. Advances in high-resolution cryo-electron microscopy (cryo-EM) require the development of validation metrics to independently assess map quality and model geometry. We report EMRinger, a tool that assesses the precise fitting of an atomic model into the map during refinement and shows how radiation damage alters scattering from negatively charged amino acids. EMRinger ( https://github.com/fraser-lab/EMRinger ) will be useful for monitoring progress in resolving and modeling high-resolution features in cryo-EM.